Evidence that BDNF regulates heart rate by a mechanism involving increased brainstem parasympathetic neuron excitability. (10th February 2014) - Wan, Ruiqian; Weigand, Letitia A.; Bateman, Ryan; Griffioen, Kathleen; Mendelowitz, David; Mattson, Mark P.
Abstract Autonomic control of heart rate is mediated by cardioinhibitory parasympathetic cholinergic neurons located in the brainstem and stimulatory sympathetic noradrenergic neurons. During embryonic development the survival and cholinergic phenotype of brainstem autonomic neurons is promoted by brain‐derived neurotrophic factor (BDNF). We now provide evidence that BDNF regulates heart rate by a mechanism involving increased brainstem cardioinhibitory parasympathetic activity. Mice with a BDNF haploinsufficiency exhibit elevated resting heart rate, and infusion of BDNF intracerebroventricularly reduces heart rate in both wild‐type and BDNF+/− mice. The atropine‐induced elevation of heart rate is diminished in BDNF+/− mice and is restored by BDNF infusion, whereas the atenolol‐induced decrease in heart rate is unaffected by BDNF levels, suggesting that BDNF signaling enhances parasympathetic tone which is diminished with BDNF haploinsufficiency. Whole‐cell recordings from pre‐motor cholinergic cardioinhibitory vagal neurons in the nucleus ambiguus indicate that BDNF haploinsufficiency reduces cardioinhibitory vagal neuron activity by increased inhibitory GABAergic and diminished excitatory glutamatergic neurotransmission to these neurons. Our findings reveal a previously unknown role for BDNF in the control of heart rate by a mechanism involving increased activation of brainstem cholinergic parasympathetic neurons <boxed-text content-type="graphic" id="jnc12656-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> Mice with reduced BDNF levels exhibit elevated heart rate, and infusion of BDNF into the brain normalizes heart rate by a mechanism involving increased brainstem cardioinhibitory parasympathetic activity. Recordings from pre‐motor cholinergic cardioinhibitory vagal neurons (CVNs) in the nucleus ambiguus indicate that BDNF increases CVN activity by increasing excitatory glutamatergic and decreasing inhibitory GABAergic neurotransmission to these neurons. Perhaps factors that increase parasympathetic tone (e.g., exercise) reduce resting heart rate, in part, by a BDNF‐mediated mechanism.